2013
DOI: 10.1111/jicd.12023
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of passion fruit juice as an endodontic irrigant compared with sodium hypochlorite solution: an in vitro study

Abstract: The PFJ alcoholic and aqueous extracts had an antibacterial effect against E. faecalis. As PFJ shows promising results, further research in this field could lead to much better results as compared to NaOCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…A study suggested that extracts from passionfruit have been used widely in traditional medicine in South America to treat anxiety, insomnia, bronchitis, and asthma . Some recent studies reported that passionfruit juice had an antibacterial effect against Enterococcus faecalis . Pineapple juice is safe and decreases inflammation severity, incidence and multiplicity of inflammation‐associated colonic neoplasia .…”
Section: Introductionmentioning
confidence: 99%
“…A study suggested that extracts from passionfruit have been used widely in traditional medicine in South America to treat anxiety, insomnia, bronchitis, and asthma . Some recent studies reported that passionfruit juice had an antibacterial effect against Enterococcus faecalis . Pineapple juice is safe and decreases inflammation severity, incidence and multiplicity of inflammation‐associated colonic neoplasia .…”
Section: Introductionmentioning
confidence: 99%
“…The thick exopolysacharide slime layers of P. aeruginosa biofilms were the reason why that problematic microorganism could not be eradicated by means of lasers; bacterial death was only 1.5 log 10 . Laser therapy can be used for different procedures in various fields of dentistry, including endodontic interventions …”
Section: Discussionmentioning
confidence: 99%
“…The word “laser” is an acronym for “light amplification by stimulated emission of radiation”. Laser energy is an effective tool for reducing the number of microorganisms in infected canals and for fighting the endodtoxin produced by Gram negatives …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different methods of combating E. faecalis were explored through the use of different irrigants. "Out of the box" treatments were evaluated for use against E. faecalis, such as the use of passion fruit juice as an endodontic irrigant 15 as well as the use of lasers and phytomedicine. 16,17 Probiotics hold a potential avenue of more common and broad use for antibacterial treatment in the future.…”
mentioning
confidence: 99%